2009
DOI: 10.1177/0145721709333269
|View full text |Cite
|
Sign up to set email alerts
|

Translating the Diabetes Prevention Program Into Practice in the General Community

Abstract: The findings suggest that it is feasible to recruit and retain high-risk participants and achieve weight loss and physical goals in a group setting that are comparable with those achieved in the DPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(56 citation statements)
references
References 29 publications
0
56
0
Order By: Relevance
“…The largest community-based translation study published to date reported achieving weight loss goals nearly identical to those of the DPP 10 . During the 16-week intervention, weight loss was 6.7%, and 45% of the 293 participants lost 7% or more of their body weight.…”
Section: Barriers To Identification Of Persons With Pre-diabetesmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest community-based translation study published to date reported achieving weight loss goals nearly identical to those of the DPP 10 . During the 16-week intervention, weight loss was 6.7%, and 45% of the 293 participants lost 7% or more of their body weight.…”
Section: Barriers To Identification Of Persons With Pre-diabetesmentioning
confidence: 99%
“…One can only speculate about why progress in the US has been slow, but a combination of factors including concerns about clinician workload, a bias toward requiring prevention activities to be cost-saving rather than cost-effective, little precedent for effective clinical-community partnerships, and uncertainty about the direction of health care reform likely account for the lack of progress. There is now increasing evidence, however, that structured lifestyle intervention programs conducted in US communities, and outside the walls of the clinical sector, can closely approximate the weight losses achieved during active intervention in the highly efficacious DPP diabetes prevention trial 10,29 , and at substantially lower cost 39 . However, no organized effort, even on a pilot demonstration basis, currently exists to design, develop, and evaluate the impact of practical referral mechanisms between primary care and community-based lifestyle programs for diabetes prevention.…”
Section: What Is Needed To Improve Identification and Prevention In Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is preventable through dietary changes and weight loss, increased physical activity, and other lifestyle changes [10,11], and in addition to lowering clinical measurements such as weight and glucose [11,12,13,14,15,16,17,18,19,20,21,22,23], community-based interventions modeled after the DPP have also been shown to promote health benefits such as improved nutrition and increased exercise [12,13,15,22,23,24,25,26,27,28]. DPP studies that have been translated into community settings have included various modifications to the original DPP protocol in order to address feasibility and sustainability challenges associated with the program, and to address the specific needs of the target communities in which studies are implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle intervention and delivery through telehealth A description of this intervention has been published previously [8,9,11]. Briefly, the Montana DPHHS began implementing the DPP in a group setting through multiple intervention sites in 2008.…”
Section: Settingmentioning
confidence: 99%